Revisiting the energy consumption-growth nexus for Croatia: New evidence from a multivariate framework analysis - Nela Vlahinic; Pavle Jakovac (Contemporary Economics, 2014)
This paper applies the most recently developed autoregressive distributed lag (ARDL) co-integration procedure to re-investigate co-integration and the causal relationship between energy consumption and real GDP within a multivariate framework that includes capital stock and labor input for Croatia during the 1952 - 2011 period. The empirical results fully support a positive long-run co-integrated relationship between production inputs and real GDP and the important role of energy in economic growth. It is found that a unidirectional causality runs from total final energy consumption to real GDP in the long run and that a bidirectional causality in the short run, which means that energy is a necessary requirement for economic growth. Additionally, the reduction in energy consumption could adversely affect GDP in the short and long run. Therefore, Croatia should adopt a more vigorous economic policy aimed toward increasing investments in installed energy capacities and reforming the economic structure towards re-industrialization and more energy-efficient industries.
Keywords: Q43; 330; economic growth; energy consumption; ARDL; Croatia